Green Human Resources Management in Industrial Companies on Sustainable Business: Conceptual Approach - M. Sani Dwi Novida Ismuladi; Ni Gusti Ayu Eka Lovita Dewi; Annisa Fitri Anggraeni; Winna Winna (Journal of Innovative and Creativity, 2025)
As global environmental issues such as climate change, environmental degradation, and excessive exploitation of natural resources become increasingly urgent, companies, especially in the industrial sector, are encouraged to adopt more sustainable business strategies. One approach that is gaining popularity is Green Human Resource Management (GHRM), a human resource management approach that integrates environmentally friendly principles and values. This study aims to examine the concept of GHRM in the context of industrial companies and its role in supporting business sustainability. The method used is a literature review, analyzing various national and international scientific articles published between 2020 and 2025. The results of the study show that the implementation of GHRM has a positive impact on pro-environmental employee behavior, operational efficiency, company image, and long-term organizational sustainability. Furthermore, this study identifies that the GHRM approach is based on the Resource Based View, Dynamic Capabilities, Stakeholder Theory, and AMO Theory. In conclusion, GHRM is not merely a complementary strategy but is crucial for industrial companies facing sustainability demands amid global competition.